1969
DOI: 10.1084/jem.130.6.1367
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Immunological Complexes Fixing Ss1c (C3) in Germinal Centers of Lymph Nodes

Abstract: 28 human and 60 experimentally stimulated rabbit lymph nodes were studied by means of light microscopy and immunofluorescence. 21 of the 28 human lymph nodes showed well-developed germinal centers. IgM, IgG, and the ß1C component of complement were found in the same distribution within germinal centers when examined in serial cryostat sections. 36 rabbits were stimulated with Brucella antigen, and 24 rabbits with BSA. A strikingly consistent correlation between distribution and appearance of specific staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1971
1971
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 52 publications
1
19
1
Order By: Relevance
“…to human IgG, IgM, IgA, C3 (,B-1C globulin), fibrinogen, and albumin by the direct technique as previously described (14,15). Sections were stained with rabbit antihuman AHF and rabbit antihuman a-2 macroglobulin by the indirect technique using fluorescein-conjugated monospecific goat antirabbit IgG as previously described (13).…”
Section: Methodsmentioning
confidence: 99%
“…to human IgG, IgM, IgA, C3 (,B-1C globulin), fibrinogen, and albumin by the direct technique as previously described (14,15). Sections were stained with rabbit antihuman AHF and rabbit antihuman a-2 macroglobulin by the indirect technique using fluorescein-conjugated monospecific goat antirabbit IgG as previously described (13).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue from 97 patients was available for this study. Rabbit antisera produced according to methods previously described (7,8) were tagged with fluorescein isothiocyanate (FITC) by the method of Wood, Thompson, and Goldstein (9), as modified in our laboratory (8). Two FITC-tagged antisera to human C3 were used, one prepared by immunizing rabbits with human 81C isolated according to Miiller-Eberhard, Nilsson, and Aronsson (10) (referred to in this publication as anti-flC), the other with 81C absorbed to zymosan (11) (referred to as anti-fi1C-Z).…”
Section: Methodsmentioning
confidence: 99%
“…After 5 wk a booster injection was given and the rabbits were bled on several occasions. IgG was isolated from the antiserum and labeled with FITC (8,9). The specificity of the anti-properdin, anti-p1,C and anti-,fiC-Z sera was studied by absorption, double diffusion in agar (14), and immunoelectrophoresis (15 Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The discovery of an interaction between lymphocytes and the fixed C3 component of complement (2)(3)(4)(5), and the demonstration by Nussenzweig et al that C3 receptors are a feature of B-cell populations (6)(7)(8)(9)(10), raise the possibility that C3 might play a part in this process (11). Germinal centers of lymphoid tissue, in which the induction of antibody production m a y occur, contain B cells, fixed C3, and complexes capable of fixing C3 (12). I have previously shown that treatment of mice in vivo with the C3-cleaving protein of cobra venom (CoF) 1 suppresses thymus-dependent but not thymus-independent antibody production, suggesting a possible role for C3 in lymphocyte cooperation (11).…”
Section: (From the Department Of Pathology University Of Cambridge mentioning
confidence: 99%